Aplikasi Campus Learning System iOU (integrated Online Ujian) Dalam Mendukung Kegiatan iLearning Education (iDu) Pada Perguruan Tinggi - Untung Rahardja; Muhamad Yusup; Qurotul Aini (CCIT Journal, 2014)
To determine the quality of a student after going through the learnig process is to test the application on an ongoing basis in order to fix the quality of education. In the world of education universities that have implemented such Raharja learning methods iLearning. But the concept of exams are generally still using paper based which is not in accordanca with the current technological advances. Altenative handling this problem is to implement a campus based learning system of cumputer based iOU. With iOU based computer based students can work on the problems on a computer random exam questions, which also makes the students can work on the problems at the same time but each working on different. In this work there is also a matter of iOU starting adn ending time limit such questions. In the paper, identified al least 5 problems faced regarding the concept paper based exam, the definition of iOU based computer based., and the benefit of this concept iOU exam. The final result of this study can be used to provide improved quality of examinations in universities Raharja to always provide convenience in doing the exam students and faculty in the terms og giving value to students.